Hermeneutika Hadist: Studi Pemikiran Muhammad Iqbal - Tenda Budiyanto (LPPM STAIS Dharma Indramayu, 2020)
Iqbal is a reformer who is unique. He is a talented poet, also a creative philosopher. He is also recognized in history that his thoughts are indeed brilliant. Especially in his thoughts about the decline and progress of Muslims who have an influence on the reform movement in Islam. Iqbal has paid close attention to what is happening to Muslims in India and Pakistan in particular, generally the Muslim world as a whole. Iqbal's study of the Hadith is based on the situation and conditions of society that developed at that time. This view, amidst the tugging of the position of the Hadith as a source of law between Muslims on the one hand, and the Orientalists on the other hand which continues to this day. Of course the intentions and understandings departing from the study are also different. Muslims are based on a great sense of responsibility towards the teachings of Islam. Whereas Orientalists study it only for scientific purposes, sometimes even just to look for weaknesses of Islamic teachings.